Pregelatinized green banana flour snack bars: Physicochemical properties, sensory quality, and gastroprotective potential in an ethanol-induced ulcer model - Thammarat Kaewmanee; Surasak Limsuwan; Sineenart Sanpinit; Pinanong Na-Phatthalung; Samuel Abiodun Kehinde; Acharaporn Issuriya; Sasitorn Chusri (PLoS ONE, 2026)
Peptic ulcers remain a recurrent gastrointestinal disorder requiring preventive nutritional strategies. Functional foods that promote gastrointestinal health may play an important role in preventing and managing peptic ulcers. In this study, we evaluated pregelatinized green banana flour (GBF) prepared by drum drying as a functional ingredient for developing snack bars with gastroprotective potential. The aim of this study was to systematically investigate how drum-drying pregelatinization influences the physicochemical and gastroprotective properties of GBF and to determine its suitability as a functional ingredient in the formulation of shelf-stable, consumer-acceptable snack bars. The pregelatinization process significantly reduced the moisture content and water activity, while improving water solubility index and swelling power. Snack bars formulated with 40% pregelatinized GBF (sPreF3) showed the most desirable sensory profile, achieving high hedonic scores for crunchiness (7.470 ± 0.860) and overall appearance (7.40 ± 0.93) on a 9-point scale. During six weeks of storage at 25 °C and 50–70% relative humidity, the product maintained stable moisture content (3.190–4.150%), low microbial counts (< 1.2 × 10² CFU/g), and consistent sensory acceptability. In vivo, both native GBF and pregelatinized GBF (1,000 mg/kg) significantly reduced ethanol-induced gastric ulcer area (0.020 ± 0.010 cm² and 0.090 ± 0.030 cm², respectively) compared with vehicle controls (0.410 ± 0.090 cm²; p < 0.05), while increasing gastric mucin levels (26–27 µg/g tissue) and pH (4.5–5.0). This finding indicates that pregelatinized GBF exhibits significant gastroprotective benefits and excellent functional and sensory qualities, supporting its potential application in gastrointestinal health–promoting snack formulations.